a TRIK JITU MEMILIH JURUSAN DI PERGURUAN TINGGI BAGI SISWA SMA DI JAKARTA BARAT: TRIK JITU MEMILIH JURUSAN DI PERGURUAN TINGGI BAGI SISWA SMA DI JAKARTA BARAT - Febrian, Wenny Desty Febrian (Andhara, 2023)
Choosing is part of a problem-solving effort as well as part of the decision-making process. The impact of making a choice will have a short/long term effect, both in the form of benefits and risks. Likewise, choosing a college is a decision that will have an impact on one's future. The decision-making process includes goal setting, problem-solving and analysis, alternative search, optimal selection of alternatives, in the implementation of decisions and assessment and monitoring. taken will be more effective. At the end of the service implementation, students are expected to be able to apply the knowledge gained to prepare for entering Higher Education later. Keywords: Choosing Majors, Majors in Higher Education